Time and Motion Study Untuk Menghilangkan Bottleneck - Mauluddin, Yusuf; Indriyani, Sagita Aulia (Jurnal Kalibrasi, 2025)
CV. XYZ is a company engaged in the garment manufacturing industry, specifically in the production of Muslim clothing. The problem faced by CV. XYZ is the failure to meet production targets. The inability to achieve hourly production targets is due to the presence of bottlenecks at several workstations. A bottleneck is a term used to describe a condition where a workstation has a lower capacity than the production requirements. The aim of this research is to identify and analyze the factors causing bottlenecks in the production process at CV. XYZ. The method used to address this issue is the Time and Motion Study method. The new working method was derived from the process of identifying movements and work times. The results showed that bottlenecks could be resolved by improving the working method. One way to minimize bottlenecks is by designing a new working method, which is achieved by eliminating ineffective and inefficient activities or work elements. The implementation of the time and motion study method successfully increased production efficiency compared to the previous method. This is reflected in the reduction of the production cycle time from 300 seconds to 158 seconds. The application of time and motion studies in this research has made a significant contribution to the development of production management theory, particularly in understanding the impact of bottlenecks on company performance. Therefore, the results of this study can serve as a reference for manufacturing companies in identifying and addressing bottlenecks in the production process.